IMPLEMENTASI METODE FISHER YATES SHUFFLE PADA COMPUTER BASED TEST ONLINE BERBASIS WEBSITE - Izzah, Asamillatul; Mufarrihah, Iftitaahul (Inovate, 2023)
Examination are one of the evaluation processes in learning. The implementation of the examination is abenchmark to measure one's achievement and ability in the learning process. The evaluation stage can be donethrough a computerized system. The Computer Based Test (CBT) system is becoming increasingly popular as anevaluation method to test students' digital abilities and is more efficient, requiring less time and cost.One important aspect of Computer Based Test (CBT) is the use of question shuffling to prevent cheating bystudents. The Fisher-Yates Shuffle method has been proven to be an effective and efficient shuffling method, inwhich the question sequence presented to students varies. This method is implemented to ensure that everystudent receives a different question sequence.In this research, a Computer Based Test (CBT) system will be developed using the Fisher-Yates Shuffle methodas the question shuffling method. This system will be implemented using PHP programming language andMySQL database. A trial will be conducted with a group of students to evaluate the performance andeffectiveness of the system simultaneously.Keywords: Implementation, Computer Based Test, Fisher-Yates Shuffle.